Наследство Достоевского - Фудель С. И. (Русский путь, 1998)
Экземпляры: ФИЛ (19991020) / Инвентарный номер: 1033486 / Цена: 42.50 / Сис.шифр: 83.3(2=Рус)1-8 / Авт.знак: Ф 94 / ГРНТИ: 17 / ББК: 83.3(2=Рус)1-8